2017
DOI: 10.1097/inf.0000000000001373
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Among Uropathogens That Cause Childhood Community-acquired Urinary Tract Infections in Central Israel

Abstract: In this retrospective study 829 positive urine cultures were analyzed. Escherichia coli bacterium was the leading uropathogen (86%). Almost 60% were resistant to ampicillin and first generation cephalosporins, and about 30% of them resistant to amoxicillin-clavulanic acid and trimethoprim-sulfamethoxazole. Almost none of them were resistant to second and third generation cephalosporins, aminoglycosides, ciprofloxacin or nitrofurantoin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…This study showed that bacterial pathogens causing UTI among diabetics exhibit high multi-drug resistance rates. This has also been revealed in different studies conducted in various regions like Sudan, United Arab Emirates, Ethiopia, Libya, Australia and Israel [6, 9-13]. A study carried out in Ethiopia showed that over 60% of the isolated E. coli was resistant to ampicillin [10].…”
Section: Discussionmentioning
confidence: 69%
“…This study showed that bacterial pathogens causing UTI among diabetics exhibit high multi-drug resistance rates. This has also been revealed in different studies conducted in various regions like Sudan, United Arab Emirates, Ethiopia, Libya, Australia and Israel [6, 9-13]. A study carried out in Ethiopia showed that over 60% of the isolated E. coli was resistant to ampicillin [10].…”
Section: Discussionmentioning
confidence: 69%
“…Another study performed in Israel during the years 2007-2014 reported ceftriaxone resistance rates of common pathogens to be £4.2%. 25 Similarly, a study published in 2013 in the USA reported on a resistance rate of less than 2% among 25,418 outpatient urinary isolates. 2 In our study, the yearly resistance rates to gentamicin remained stable and never exceeded 9%.…”
Section: Figmentioning
confidence: 97%
“…A retrospective study performed in 2017 in Israel, on 829 pediatric urinary isolates, found that the resistance rate of E. coli to ampicillin and first-generation cephalosporins reached *60% and to amoxicillin/clavulanate and TMP-SMX, nearly 30%. 25 During the years 2010-2017, over 30% of the isolated bacteria were resistant to ampicillin, with an increasing trend ( p = 0.0044) from 33.3% in 2010 to a peak resistance rate of 76.4% in 2014. According to our results, ampicillin should remain as a treatment, specifically for UTIs caused by Enterococcus spp.…”
Section: Figmentioning
confidence: 98%
“…6 Aggressive treatment of UTI is mandatory in children within 3 days of arrival in OPD to prevent renal damage (when culture sensitivity report is awaited), delay in treatment often leads to increased severity of infection with greater incidence of renal damage. 7 Etiology and resistance pattern of urinary tract infection acquired through community is generally not available and if available is outdated as resistance pattern of bacteria to antimicrobials often changes periodically in a given region. The etiological agents responsible for causing UTI are different in different region and their variability changes with geographical location, time and age of the patients.…”
Section: Introductionmentioning
confidence: 99%